Guidelines for Use of Propeller-type Irrigation Water Meters - Rogers, Danny H.; Black, Richard D. (My University, 1992)
A guide to selecting, installing, and using a propeller-type irrigation meter.
L869_1992-09
Keywords: L869; Equipment and Structures; Crops; L